2020
DOI: 10.1109/access.2020.2977675
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Heading Accuracy for GPS/INS by Employing Average Velocity in Low Dynamic Situations

Abstract: In this paper, we proposed an algorithm that improves the heading accuracy of the global positioning system (GPS)/inertial navigation system (INS) integrated system used in automobiles by manipulating INS velocity and GPS velocity measurements. Two velocities are provided by the GPS receiver: the velocity calculated using the position difference and the velocity calculated using the Doppler shift. The velocity obtained using the position difference is an average velocity for a certain time period, which is ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The course angle of vehicle and course measure flag is shown in Figure 11. It can be found that the course measure flag varies frequently from 0 to 1 according to the judgment criteria set in (12), where 0 means GNSS course angle is not used as measurement and 1 means GNSS course angle is used as measurement. From the system dynamic (6) and measurement equation (10), we can find that if no measurement is used in the Kalman filter the IMU mounting angles and vehicle scale factor will remain unchanged since they only appear in the measurement equation (10).…”
Section: Experiments Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The course angle of vehicle and course measure flag is shown in Figure 11. It can be found that the course measure flag varies frequently from 0 to 1 according to the judgment criteria set in (12), where 0 means GNSS course angle is not used as measurement and 1 means GNSS course angle is used as measurement. From the system dynamic (6) and measurement equation (10), we can find that if no measurement is used in the Kalman filter the IMU mounting angles and vehicle scale factor will remain unchanged since they only appear in the measurement equation (10).…”
Section: Experiments Resultsmentioning
confidence: 99%
“…A simple criteria to judge whether the vehicle is traveling in straight line is shown in (12). The angular rate of IMU z axis is used to determine whether the vehicle travels in straight line, where VSFL represents the vehicle straight line flag.…”
Section: Vehicle Straight Line Driving Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first test aimed at assessing the improvement in attitude and position estimation granted by the redundant configuration; for this set of tests, all the available position and speed values of the GNSS have been considered. Heading, pitch and roll provided by both prototype and single SensorTile TM have been compared with the attitude estimates granted by the STIM300; in particular, results shown in Figure 12 are associated with the heading angle, i.e., the one most difficult to be estimated due to observability issues [ 38 , 39 ]. Even though the prototype outputs appeared to be slower to converge with respect to the reference IMU, it is worth noting the remarkable concurrence experienced for time intervals greater than 400 s. In particular, in the route section referred to as straight in Figure 11 , average differences between prototype and STIM300 angle estimates results as low as 0.025rad have been encountered.…”
Section: Resultsmentioning
confidence: 99%